ENHANCING STUDENTS’ WRITING SHORT STORY USING TOPICAL PERSPECTIVE TECHNIQUE - Mar’atul Azizah (Universitas Islam Ogan Komering Ilir Kayuagung, 2019)
This study investigated whether topical perspective technique wasable to improve students’ writing achievement or not and to know the students’ perception toward topical perspective technique in improving students’ writing achievement. Quasi-experimental method and nonrandomized control-group pretest-posttest design were used in this study. The whole population was the eleventh-grade students of MA Al AqidahKutapandan taken as the sample consisted of thirty students. The data were collected by a written test which asked students to write a composition and was evaluated by using short story scoring rubric and questionnaire in order to know students’ perception toward topical perspective in improving writing achievement. Since the sampling method used the study population, so the data obtained were analyzed by using gained score. The findings showed that students who were exposed by using topical perspective technique had higher mean of a gained score (6.48) compared to students who were not exposed (2.19). It meant that topical perspective technique was able to improve students’ writing achievement. Based on the questionnaire given, it could be inferred that most of the students thought that topical perspective helped the students to respond the story they read so that they could improve their writing ability and fond of writing after using topical perspective technique. It meant that the students’ perception toward topical perspective technique in improving writing achievement were better than before